Tinjauan Terhadap Penyelenggaraan Angkutan Sewa Khusus Di Provinsi Nusa Tenggara Barat Berdasarkan Peraturan Menteri Perhubungan Nomor 118 Tahun 2018 - Raden Mochammad Hazrat Rachmatullah; Lalu Hadi Adha (Private Law, 2022)
The purpose of this study was to determine the implementation of special rental transportation in West Nusa Tenggara Province and to determine the extent of legal protection for users of special rental transportation services based on Minister of Transportation Regulation No. 118 of 2018. This thesis research uses empirical juridical research methods. The results of this study indicate that the Regional Government of West Nusa Tenggara Province has not adjusted the provisions regarding special rental transportation with Minister of Transportation Regulation No. 118 of 20118, this can be seen in the absence of changes and/or replacement of Perda No. 6 of 2018. Furthermore, in Article 32 paragraph (1) and paragraph (2) of the Minister of Transportation Regulation No. 118 of 2018 it is stated that public protection in special rental transportation services is given to passengers and drivers. Meanwhile in Permenhub No. 108 of 2018 in conjunction with Regional Regulation No. 6 of 2018 does not clearly regulate legal protection for the public using special rental transportation.